Perception and Behavior of Voting Public After the 2019 Election in Indonesia - Nazira, Siti; Zetra, Aidinil; Asrinaldi, Asrinaldi; Rusta, Andri (ARISTO, 2024)
Simultaneous general elections will be held in 2024 with the theme of combining national and local elections in the same year. This is done based on the Constitutional Court Decision Number 14/PUU-11/2013 on simultaneous elections, which aims to minimize state financing in the implementation of elections, minimize high-cost politics for election participants, as well as money politics involving voters, abuse of power or prevent bureaucratic politicization, and streamline government work schemes. The purpose of this research is to discuss the dynamics of changes in people's perceptions and voting behavior after the 2019 elections in Indonesia from a political perspective. In voting behavior, one of the perspectives used in mapping and describing the patterns of changes in voting behavior and determining political choices in general elections uses the voting behavior approach. Studies related to voting behavior are studies related to studies that aim to reveal several reasons or factors that cause a person to tend to choose a party or contestant. This research uses quantitative methods. Meanwhile, the sample was drawn randomly using multistage random sampling. The total sample amounted to 1,240 samples, with PSUs in the Province. The survey population is the entire population aged 17 years and over or married. The survey was conducted in 34 provinces in Indonesia. According to the results of the research, Prabowo Subianto still remains the strongest presidential candidate compared to the other candidates. Then, the tendency of Indonesian people to vote for parties, PDIP has the highest vote compared to the tendency towards other parties. Then the dynamics of changing perceptions after the 2019 election, the voting behavior of the Indonesian people tends towards the school of rational choice.